PENGGUNAAN METODE COURSE REVIEW HORAY (CRH) UNTUK MENINGKATKAN PEMBELAJARAN IPS TENTANG PERJUANGAN MELAWAN PENJAJAHAN SISWA KELAS V SD NEGERI 1 KARANGSARI TAHUN AJARAN 2013/2014 - Winarsih, May (KALAM CENDEKIA PGSD KEBUMEN, 2017)
The use of Course Review Horay (CRH) method to improve the social science learning about the struggle to resist the colonization for the fifth grade students of SD Negeri 1 Karangsari in academic year 2013/2014. The purposes of this research are to improve the social science learning process and learning outcomes about the struggle to resist the colonization. This research was Classroom Action Research technique and implemented in three cycles. The result of this study demonstrate that: the use of Course Review Horay (CRH) method can improve the learning process carried out by the teacher with the result that improved continuously at each cycle. Student learning outcomes also improved continuously with the highest average score can be achieved in the third cycle. Keywords: method, course review horay, social science learning